INOVASI PRODUK GULA MERAH TEBU PADA KSU-ED TABEK, NAGARI TALANG BABUNGO - Andasuryani, Andasuryani; Adrizal, Adrizal; Chandra, Alhapen Chandra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Indragiri, 2022)
The molding process using coconut shells created unstandardized brown sugar in terms of shape and size, less competitive, limited market by Koperasi Serba Usaha Ekonomi Desa (KSU ED) Tabek. This activity aimed to motivate KSU-ED Tabek to produce brown sugar, which has a different and attractive appearance. The activity was carried out in the form of lectures, discussions, and demonstrations, starting from providing the molding equipment, introducing several innovations of brown sugar shape and size, product innovation by adding spices, and demonstration of packaging of brown sugar for members of KSU-ED Tabek. During the activity, members of KSU-ED Tabek showed a positive response which was shown by their enthusiasm in discussing various innovations in mold shapes and sizes, product flavor innovations, and brown sugar packaging. This community service activity has could increase the innovative and creative spirit of KSU-ED Tabek members in developing brown sugar businesses.